2015
DOI: 10.7705/biomedica.v36i1.2795
|View full text |Cite
|
Sign up to set email alerts
|

Predicción de sensibilidad a la warfarina basada en VKORC1 y CYP2C9 en pacientes de diferentes lugares de Colombia

Abstract: Contribución de los autores:Ricardo A. Cifuentes: concepción del proyecto, genotipificación y análisis de datos Todos los autores participaron en la captación de los pacientes, la recolección de datos, la interpretación de los resultados y la escritura del manuscrito.Predicción de la sensibilidad a la warfarina con base en polimorfismos de los genes VKORC1 y CYP2C9 en pacientes colombianos Introducción. La validación de los factores predictores de la sensibilidad a la warfarina es importante para evitar las he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
3
2
0
Order By: Relevance
“…A meta‐analysis by Tang et al ., which encompassed 53 studies, reported that GA and GG carriers required 45% (95% CI 42–49) and 77% (95% CI 70–84) higher doses of warfarin, respectively, compared to homozygous carriers of VKORC1 –1639 AA 16 . Similar findings have been observed in studies conducted in several Latin American countries, including Brazil, 26–29 Colombia 30–32 and Chile, 33 which are consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A meta‐analysis by Tang et al ., which encompassed 53 studies, reported that GA and GG carriers required 45% (95% CI 42–49) and 77% (95% CI 70–84) higher doses of warfarin, respectively, compared to homozygous carriers of VKORC1 –1639 AA 16 . Similar findings have been observed in studies conducted in several Latin American countries, including Brazil, 26–29 Colombia 30–32 and Chile, 33 which are consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…higher doses of warfarin, respectively, compared to homozygous carriers of VKORC1-1639 AA. 16 Similar findings have been observed in studies conducted in several Latin American countries, including Brazil, [26][27][28][29] Colombia [30][31][32] and Chile, 33 which are consistent with our study.…”
Section: Nomenclature Of Targets and Ligandssupporting
confidence: 92%
“…These results are consistent with the frequencies found in the VKORC1 promoter, CYP2C9*2, and CYP2C9*3 in patients undergoing Warfarin treatment in Bogota, the capital of Colombia. [19,20] Our findings indicate that despite the slight difference found between these 2 cities, the frequencies of the analyzed alleles were similar.…”
Section: Discussionsupporting
confidence: 49%
“…The number of patients with heterozygous or homozygous CYP4F2*3 is depicted in superscript. Colombian regions) [20] 112/148 (56. The genetic frequencies of VKORC1*2, CYP2C9*2, CYP2C9*3, CYP4F2*3, and rs12777823 found in our samples are similar to the ones shown for Latin Americans of European and Native American Ancestry and European populations; however, there are distinct differences with Latin Americans of Afro-Caribbean ancestry or African, African American, and South Asian populations (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation